2018
DOI: 10.1038/s41598-017-19079-y
|View full text |Cite
|
Sign up to set email alerts
|

Development and optimization of a differentiated airway epithelial cell model of the bovine respiratory tract

Abstract: Cattle are subject to economically-important respiratory tract infections by various bacterial and viral pathogens and there is an urgent need for the development of more realistic in vitro models of the bovine respiratory tract to improve our knowledge of disease pathogenesis. In the present study, we have optimized the culture conditions in serum-free medium that allow bovine bronchial epithelial cells (BBECs) grown at an air-liquid interface to differentiate into a three-dimensional epithelium that is highl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(69 citation statements)
references
References 78 publications
3
66
0
Order By: Relevance
“…30 Of note, on thick scaffolds (over 300 µm), we did not see formation of mucociliary pseudostratified epithelium even after HA treatment. 31,32 Our results are in line with these reports. Previously, it was shown that the differentiation of the tracheal epithelium depends on the porosity of the scaffold used.…”
Section: The Role Of Matrix Thickness and Permeabilitysupporting
confidence: 93%
See 1 more Smart Citation
“…30 Of note, on thick scaffolds (over 300 µm), we did not see formation of mucociliary pseudostratified epithelium even after HA treatment. 31,32 Our results are in line with these reports. Previously, it was shown that the differentiation of the tracheal epithelium depends on the porosity of the scaffold used.…”
Section: The Role Of Matrix Thickness and Permeabilitysupporting
confidence: 93%
“…32 Many of these factors are directly secreted by resident fibroblasts or are under fibroblast expressional control. 32 Many of these factors are directly secreted by resident fibroblasts or are under fibroblast expressional control.…”
Section: Co-cultivation Of Airway Epithelial Cells With Fibroblastsmentioning
confidence: 99%
“…Cozens et al found an EGF concentration of 10 ng/mL most suitable for bovine bronchial epithelium 40 . As mAir was supplemented with EGF to a concentration of 10 ng/mL, our results support their findings.…”
Section: Discussionmentioning
confidence: 99%
“…Bovine bronchial epithelial cells can be stimulated to differentiate into a more representative model of the in vivo microenvironment through exposure to the atmosphere [36, 37, 59]. The methodology for differentiation of bovine airway epithelial cells have been fully optimised [44] and the model well-characterised [45]. The differentiated BBEC model has been shown to replicate the hallmark defences of the respiratory tract, including active mucocilary clearance.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously investigated the growth conditions required for optimal growth and differentiation of bovine bronchial epithelial cells at an ALI [44] and assessed the temporal differentiation of these cells to identify an optimum window suitable for infection studies [45]. The aim of the present study was to investigate the interactions of a panel of M. haemolytica isolates, representing virulent and commensal strains recovered from both cattle and sheep, with differentiated bovine bronchial epithelial cells grown at an ALI.…”
Section: Introductionmentioning
confidence: 99%